Bio-Synthesized Zinc Oxide Nanoparticles Using Plant Extracts - Mohammad, Ahmad Zulfaqar; Ainuddin@Nordin, Ainun Rahmahwati (Research Progress in Mechanical and Manufacturing Engineering, 2022)
In this day and age, nanoparticles have become one of the essential needs of society invarious sectors such as development. Another applications have the potential to beused with ZnO, therefore the development can improve the quality of nanoparticles tomake them more specific. Synthesis procedures should avoid the use of harmfulchemicals to ensure that the environment is maintained. The green biosynthesismethod is a simple procedure where the plants used are easy to find and where themethods used are safe. In this paper, a brief overview of the Zinc Oxide Nanoparticle(ZnO) method is used to identify the shape, size and characteristics found in plantextract such as coriander, brinjal and banana peel. The unresponsive effect oftemperature on ZnO during the experiment can change the size, shape andcharacteristics. To determine the characteristics of the ZnO synthesis from plantextract, machines such as XRD, FESEM and UV-Vis were used in this experiment.